Pharyngeal airway dimensions in Iranian female young adults with different skeletal patterns using cone-beam computed tomography - Amin Golshah; Tanaz Hosseini Jalilian; Nafiseh Nikkerdar (Wolters Kluwer Medknow Publications, 2023)
OBJECTIVES: To assess the oropharyngeal airway in Iranian female young adults with different skeletal patterns using cone-beam computed tomography (CBCT). MATERIALS AND METHODS: This descriptive, cross-sectional study evaluated 105 CBCT scans of female patients between 18 and 35 years retrieved from the archives of a radiology clinic. The images were evaluated in axial, sagittal, and frontal sections. In the axial plane, the maximum and minimum cross-sectional area (CSA) of the airways at the oropharynx, minimum width (anteroposteriorly), and minimum depth (laterally) were measured using Mimics Medical software. The oropharyngeal volume was measured by NemoFAB software. The values were compared among the groups with different sagittal, vertical, and transverse patterns. The correlation of indices with airway measurements was analyzed using Monte Carlo Chi-square and Pearson's correlation coefficient. RESULTS: No significant difference was noted in oropharyngeal airway dimensions and volume among cases with different skeletal sagittal, vertical, and transverse patterns (P > 0.05) except for class III patients with normal transverse pattern in whom maximum CSA in low-angle group was larger than that in normal-angle group (P < 0.05) and class I normal-angle patients in whom maximum CSA in transverse normal group was smaller than that in constriction group (P < 0.05). CONCLUSIONS: Oropharyngeal dimensions were not significantly different in Iranian female young adults with different skeletal patterns.